IMPLEMENTASI MANAJEMEN SARANA PRASARANA DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI SDN LIDAH WETAN 04 SURABAYA - Cahyani, Davina Pramesti Ragita; Anggraini, Della Rana Maulidia; Kharisma, Aisca Nindi; Kirana, Din Arsy Anindita; Firman, Muhammad Farel Maulana; Wulandari, Ayu (Universitas Negeri Jakarta, 2023)
An active and planned activity to carry out the teaching and learning process systematically that is arranged before the learning process takes place is referred to as education. Education is an important thing that is needed by everyone of all ages. Education is not just learning that must be learned, but education is also the key to improving one's self-quality. In the Surabaya City area, precisely at SDN Lidah Wetan 04 Surabaya, it is one of the schools that also has facilities and infrastructure to support learning. However, there are several obstacles so that the infrastructure facilities in this school can be said to be inadequate. In this school there are several limitations in the provision of learning support facilities and infrastructure such as computers, cctv, speakers, projectors, and LCDs. Infrastructure such as limited space is not available for mosques or prayer rooms for places of worship so that only classrooms are provided as a substitute for places of worship. Researchers obtain data using qualitative methods. This study used observation, interviews, and documentation. The purpose of the study is to find out how the management of facilities and infrastructure improves the quality of learning, how the management of current facilities and infrastructure supports learning, and how effective the use of technology in the management of facilities and infrastructure.